2022
DOI: 10.1016/j.contraception.2021.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported experience with discussion of all options during pregnancy options counseling in the US South

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Although the stigma of not intending to pursue parenthood can prevent patients from disclosing that intention, 36–38 available research indicates that patients are open to discussing their pregnancy intentions with their provider 16 and would answer honestly if asked 8 . Discussion of all options during pregnancy options counseling was associated with a more positive patient experience in prior research 23 . However, unpublished program evaluation data indicates that many providers prefer not to discuss alternatives to parenting unless a patient “expresses despair” about pregnancy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the stigma of not intending to pursue parenthood can prevent patients from disclosing that intention, 36–38 available research indicates that patients are open to discussing their pregnancy intentions with their provider 16 and would answer honestly if asked 8 . Discussion of all options during pregnancy options counseling was associated with a more positive patient experience in prior research 23 . However, unpublished program evaluation data indicates that many providers prefer not to discuss alternatives to parenting unless a patient “expresses despair” about pregnancy.…”
Section: Discussionmentioning
confidence: 98%
“…Studies suggest that non‐comprehensive pregnancy options counseling favors counseling around continuing pregnancy over abortion counseling. 22 , 23 Such pregnancy options counseling bias can coerce patients into continuing pregnancy, and may in turn lead them to face downstream maternal and infant mortality risks. 21 , 24 , 25 Inadequate counseling at the point of initial pregnancy confirmation may also play a role in further reducing patients' trust in medical systems, with implications for pregnancy care and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Patient preferences for pregnancy options counseling do not always match the provider's perspective and the counseling provided [6 ▪ ]. This is evident in studies showing that many providers refer their patients only to prenatal care [20] and often do not discuss or refer for abortion services [15,21].…”
Section: The Patient Perspcectivementioning
confidence: 99%
“…In a study looking at patient experiences with pregnancy options counseling, 10% of patients reported that their provider discussed all options, which included abortion, adoption, and parenting. Providers who discussed all options were more likely to have received options counseling training [6 ▪ ]. Implementation of pregnancy options counseling education and training sessions could improve pregnancy options counseling and increase the frequency of abortion referrals amongst providers who were previously reluctant or opposed to this counseling.…”
Section: Variations In Pregnancy Options Counselingmentioning
confidence: 99%
See 1 more Smart Citation